RELATIONSHIP OF THE ETHMOIDAL INFUNDIBULUM, UNCINATE PROCESS, AND NASAL SEPTUM DEVIATION WITH CHRONIC MAXILLARY RHINOSINUSITIS ON PARANASAL SINUS CT SCAN IN MEDAN - Fingga Prahasti Nasution; M.Rizky Fachri; Elvita Rahmi Daulay; Ferryan Sofyan (MEDALION Journal: Medical Research, Nursing, Health and Midwife Participation, 2026)
Background: Chronic rhinosinusitis (CRS) is a common sinonasal inflammatory disease, with global prevalence ~10,9% (European Position Paper on Rhinosinusitis and Nasal Polyps 2021). CRS pathogenesis is associated with impaired osteomeatal complex (OMC) drainage, influenced by anatomical variations, e.g. ethmoidal infundibulum (EI) length and width, uncinate process (UP) type, and nasal septal deviation (NSD) degree. This study aims to evaluate the relationship between anatomical variations of the OMC (EI, UP, and NSD) and the occurrence of maxillary CRS based on paranasal sinus (PNS) CT. Method: cross-sectional design involved 100 maxillary sinuses from patients who underwent PNS CT at Prof. Dr. Chairuddin Panusunan Lubis Hospital. Statistical analysis was performed using Chi-square and Eta correlation tests. Result: Mean EI length in CRS (5.9 ± 2.7 mm) was shorter than in non-CRS (7.8 ± 2.6 mm, p<0.001), while EI width was greater (2.8 ± 1.1 mm vs. 2.3 ± 0.5 mm, p<0.05). UP type A was most frequent in CRS (47%, p<0.001). NSD ≥10° was more common in CRS (31%) than in non-CRS (13%, p<0.05). Conclusion: Anatomical variations of OMC play an important role in predisposition to maxillary CRS. Most patients showed Keros type 2 and Gera type 2, indicating a moderate risk of complications during functional endoscopic sinus surgery. Comprehensive evaluation using PNS CT is essential for safe and effective surgical planning.